Resource Rents, Governance, and Conflict. - Collier, P; Hoeffler, A (SAGE Publications, 2005)
Case studies as well as cross-country studies suggest that countries with an abundance of natural resources are more prone to violent conflict. This collection of articles analyzes the link between natural resources and civil war in a number of different ways. So far the literature falls broadly into two camps. First, in the economics literature the well-documented "resource curse" leads to low-income growth rates and low levels of income. These in turn constitute low opportunity costs for rebellion and make civil war more likely. On the other hand, political science literature concentrates on the link between natural resources and weak institutions. States with natural resources often rely on a system of patronage and do not develop a democratic system based on electoral competition, scrutiny and civil rights. Based on further empirical evidence in this volume we conclude with a brief overview of current policy initiatives.